Behavior of Fruit And Vegetable Consumtion In Galala Village, North Oba District, Tidore Islands City - Norma B. Toduho; Mayasari Soamole; Andiani; Riskal Muslim; Riska Alim; Rukmina Armain (BIOSAINSTEK, 2025)
Food choice behavior, include fruit and vegetables consumtion, influenced by level of knowledge of the people, which ultimately has an impact on their nutritional condition. This research uses descriptive analysis with crosssectional study design. The population consist  were 1082 heads of families. The sample in this study consist were 292 heads of families obtained from sample calculations using the Slovin formula (alpha 0.05). Based on the results of descriptive analysis on fruit eating behavior variables, it can be concluded that the frequency of people consuming fruit in Galala Village every week is as follows: 144 (49.3%) respondents 1-2 times a week, 66 (22.6%) respondents 3-4 times a week, 31 (10.6%) respondents once a day, 24 (8.2%) respondents >1 time a day, and 27 (9.2%) respondents never. For the vegetable eating behavior variable, it was found that the frequency of people consuming vegetables in Galala Village every week was as follows: 134 (45.9%) respondents >1 time per day, 59 (20.2%) respondents 3-4 times a week, 52 (17.8%) respondents once a day, 45 (15.4%) 1-2 times a week and 2 (0.7%) respondents never. So it can be concluded that the fruit and vegetable eating behavior of the people in Galala village still needs to be improved. It is hoped that there will be community involvement and collaboration with health workers in efforts to increase fruit and vegetable eating behavior in Galala Village.